Differential Expression of Claudin 1 and 4 in Basal Cell Carcinoma of the Skin - T. Nakazawa; A. Hasegawa; T. Nagasaka; K. Yoshida; F. Guo; D. Wu; K. Hiroshima; M. Takeuchi (Hindawi Limited, 2023)
Basal cell carcinoma (BCC) is the most common human malignancy. The biological behavior of this entity is remarkably indolent. Claudin plays an important role in tight junctions, regulating paracellular passage of variable substance including growth factors and maintaining the polarity of epithelia. Up- or downregulated claudin expression has been reported in many cancers. Nevertheless, claudin expression in BCC of the skin remains unclear. We therefore examined the status of claudin 1 and 4 expressions in BCC and adjacent normal skin by immunohistochemistry (IHC). Our IHC results demonstrated high claudin 1 expression and low claudin 4 expression in 33 of 34 lower-grade BCCs. In lower-grade BCC, claudin 1 was increased and claudin 4 was decreased compared with the normal skin. Claudin 1 was inclined to be highly expressed in the membrane and cytoplasm of tumour cells in the periphery of tumour nest. Conversely, almost all lower-grade BCCs (33/34) and one of two higher-grade BCC lacked or showed focal positivity for claudin 4. These results imply that the expression pattern is characteristics of lower-risk BCC. Interestingly, one of the two higher-grade BCCs demonstrated the converse expression patterns of claudins, with decreased claudin 1 and increased claudin 4. The combination of immunohistochemical claudin 1 and 4 expression may offer a useful ancillary tool for the pathological diagnosis of BCC. Furthermore, membranous and intracellular claudins may present future therapeutic targets for uncontrollable BCC.